A TOTP-Based Two Factor Authentication Scheme for Hyperledger Fabric Blockchain - Park, Woo Suk; Hwang, Dong Yeop; Kim, Ki Hyung (International Conference on Ubiquitous and Future Networks, ICUFN, 2018)
In this paper, we propose a new authentication method to prevent authentication vulnerability of Claim Token method of Membership Service provide in Private BlockChain. We chose Hyperledger Fabric v1.0 using JWT authentication method of membership service. TOTP, which generate OTP tokens and user authentication codes that generate additional time-based password on existing authentication servers, has been applied to enforce security and two-factor authentication method to provide more secure services.
Keywords: Authentication methods; Authentication servers; Membership service; Secure services; Time based; TOTP; Two factor authentication; User authentication; Hyperledger Fabric; JWT; Membership service; TOTP; Two-Factor Authentication